Electronic states of mixed base pairs systems of dna and the effect of base composition and sequences on the band structures using screw axis translational symmetry. Issue 4 (8th June 2012) - Xie, Peng; Teramae, Hiroyuki; Liu, Kai; Aoki, Yuriko; Nakai, Hiromi; Yoshizawa, Kazunari; Ando, Koji; Nakajima, Takahito; Brändas, Erkki J.
Abstract We perform the conventional band structure and local density of states (LDOS) calculations in the vicinity of the Fermi level at ab initio molecular orbital level with 6‐31G base set for one DNA duplex with repeated mononucleotide sequences and four DNA duplexes with repeated dinucleotide sequences in B form neutralized by Na+. The LDOS of six other DNA duplexes with repeated trinucleotide sequences in the same states are analyzed. The obtained results are compared with those by the band calculations based on periodic boundary condition using screw axis symmetry. The investigations focused on the influence of the base composition and base sequence on the DNA conductivity. The band structure and LDOS calculation results indicated that base guanine is more important for DNA conductivity than the other bases, and DNA conductivity varies with base sequence of DNA. Moreover, poly (dG) poly (dC) shows the best conductor in our DNA duplex models. © 2012 Wiley Periodicals, Inc.